The Long Relationship of Undergoing Hemodialysis Therapy with the Quality of Life of Chronic Kidney Failure Patients at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Fadilla Sulistayani Duhe; Nurdiana Djamaluddin; Ita Sulistiani (Universitas Muhammadiyah Palu, 2026)
Chronic kidney failure is a progressive disease that causes a permanent decline in kidney function so that patients need long-term hemodialysis therapy. Hemodialysis that is carried out continuously can have physical, psychological, social, and emotional impacts that affect the patient's quality of life. This study aims to determine the relationship between long-term hemodialysis therapy and the quality of life of chronic kidney failure patients at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. This study uses a quantitative method with a cross sectional design. The population in this study is all patients with chronic kidney failure who undergo hemodialysis therapy at Prof. Dr. H. Aloei Saboe Hospital as many as 83 patients. The research sample amounted to 46 respondents who were taken using purposive sampling techniques. The instrument used was the KDQOL-SF 36 questionnaire to measure the patient's quality of life. Data analysis used the Fisher's Exact Test. The results showed that most of the respondents underwent hemodialysis >12 months, 35 respondents (76.1%), while 11 respondents (23.9%) <underwent hemodialysis 12 months). Most of the respondents had a poor quality of life, namely 38 respondents (82.6%), while 8 respondents had good quality of life (17.4%). The results of bivariate analysis using Fisher's Exact Test showed a p value = 0.013 (p < 0.05), so that there was a significant relationship between the length of time they underwent hemodialysis therapy and the quality of life of patients with chronic kidney failure at Prof. Dr. Aloei Saboe Hospital.Keywords: Nurse Support, Compliance Level, Chronic Kidney Failure Patients, Hemodialysis Therapy